A Simple and Efficient Approach to Cellulose/Silica Composite Aerogel with High Silica Utilization Efficiency - Lin, Chong; Li, Ang; Cao, Yang; Lu, Lingbin (Journal of Research Updates in Polymer Science, 2015)
Cellulose aerogel is a fascinating material with high porosity, low density and biocompatibility. However, cellulose aerogel lacks sufficient thermal stability. Recombination between cellulose aerogel with silica is efficacious for enhance the cellulose aerogel’s thermal stability. This work described a simple and efficient approach to the cellulose/silica composite aerogel via a dropwise manner, using tetraethoxysilane as silicon source and NaOH solution as cellulose solvent. The result showed that the thermal stability of cellulose aerogel was enhanced by introducing silica. And by this manner, the utilization efficiency of silica was up to 95%. The composite aerogel had a low density and a high porosity, which promised the material a good heat insulation performance, and the thermal conductivity of the composite aerogel was low to 0.0161W/(m·K). Moreover, by adjusting cellulose concentration and tetraethoxysilane amount, the density, porosity and thermal conductivity of the composite aerogel could be controlled. This work contributed to improving the utilization efficiency of silica for the composite aerogel with better performances.